Historical and Modern Forms of Alternative Dispute Resolution - Mateev, Michail (Media and Language, 2020)
This article gives a brief analysis of the characteristics of the model of legislation and state administration of justice, established in the Continental legal system, with a view to their effectiveness in regulating public relations and resolving legal disputes. A comparison is made with the historical and contemporary forms of alternative dispute resolution: the Ecclesiastical court of Christian church, justice of the peace and mediation.